ANT 2016/17: AWI airborne Accumulation Radar data over central Dronning Maund Land and around the Dome Fuji ice core site (OIR Dome F and GEA-Vb-FMA projects) - Olaf Eisen; Graeme Eagles; Daniel Steinhage; Veit Helm; Tobias Binder (PANGAEA, 2025)
This dataset contains airborne radar data acquired using the AWI Accumulation Radar (ACCU) system during the Antarctic season of 2016/17 to investiage the geodynamic evolution of East Antarctica, and for the Beyond EPICA - Oldest Ice reconnaissance around Dome Fuji. The profiles extend across the central Dronning Maud Land across the Jutulstraumen drainage basin, around the EDML ice core site and around Dome Fuji. The data are available as netCDF files (including waveforms and metadata), KML files of the profile line locations, and quicklook images of the radargrams.